Ontologi, Epistemologi dan Aksiologi dalam Filsafat untuk Pengembangan Teori Manajemen Pendidikan Islam - Nabilah Amaliyah Iqbal; Darwis Hude (At-Tadris: Journal of Islamic Education, 2026)
This study focuses on analyzing the ontological, epistemological, and axiological dimensions in Islamic educational philosophy as the basis for developing a tauhid-based Islamic educational management theory, using a qualitative approach with library research methods through critical review of works on Islamic philosophy and educational management. The results of the study show that ontologically, Islamic education places humans as creatures with innate rational and spiritual potential to be developed into perfect beings. Epistemologically, knowledge in Islam comes from the integration of revelation, reason, and empirical experience, which produces a scientific paradigm that is dialogical, rational, and spiritual. Meanwhile, axiologically, Islamic education is oriented towards prophetic values such as justice, trustworthiness, and the benefit of the people as the moral basis of educational management. The integration of these three dimensions gives rise to a transformative, participatory, and value-based paradigm of Islamic educational management that is relevant to the challenges of the digital age. Thus, this study affirms that the philosophy of Islamic education plays a strategic role in building an educational system that is scientific, spiritual, and civilized.